Investigating the PS seismic imaging of faults using seismic modelling and data from the Snøhvit field, Barents Sea - Jennifer Cunningham; Wiktor W. Weiball; Nestor Cardozo; David Iacopini (2021)
Supplementary Material 1. Technical explanation of the forward seismic models.